PENGEMBANGAN MEDIA PEMBELAJARAN SCRATCH BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN COMPUTATIONAL THINKING SISWA - Nor Nadia; Moh Zayyadi; Fetty Nurita Sari; Sri Indriati Hasanah (Program Studi Pendidikan Matematika Universitas Kuningan, 2025)
Computational thinking skills among junior high school students generally remain low, while teachers seldom combine digital learning media with local culture in mathematics lessons. An ethnomathematics-based Scratch medium offers one way to close this gap, since it makes mathematics learning more contextual, engaging, and meaningful. This study set out to build such a medium and examine whether it meets standards of validity, practicality, and effectiveness for strengthening students' computational thinking. A research and development (R&D) design was applied, following the five ADDIE stages analysis, design, development, implementation, and evaluation with eighth-grade students at SMP Negeri 1 Pragaan as participants. Data were gathered through a validation sheet, response questionnaires from teachers and students, and pretest-posttest scores, then examined descriptively alongside the N-Gain formula. The resulting media obtained a validity score of 80%-85.5% (valid), a practicality score of 75% (fairly practical), and an N-Gain of 69% in the experimental class versus 33% in the control class (fairly effective). Overall, these results suggest that ethnomathematics-based Scratch media can support junior high school students in building stronger computational thinking skills.